OUTCOMES IN EARLY TREATMENT OF CLASS II DIVISION 1 MALOCCLUSION WITH FUNCTIONAL APPLIANCES - Daniela Anistoroaei; Loredana Golovcencu; Alina Claudia Sodor; Eduard Radu Cernei; Alexandre Dinh Van Minh; Cătălina Iulia Săveanu (Romanian Dental Association for Education, 2023)
The early treatment of Class II/1 malocclusion is influenced by factors such as the severity of the anomaly, the time of initiation of orthodontic treatment, patient cooperation, treatment steps and the type of orthodontic appliance used. Early treatments act on growth by reducing skeletal discrepancies, correcting occlusal relationships, normalizing functions and allowing the sagittal growth potential of the mandible to be expressed. Functional appliances for the correction of mandibular retrognathism are effective if they are applied during the pubertal growth stage, when the effectiveness is maximum, but we must always keep in mind that the result of early treatment with functional appliances is the patient's individual response to the type of treatment used.